Digitalization Marketing of Local Farmer Product in Gaining Brand Awarness and its Impact to Intention to Buy - Hamdan Hamdan (Budapest International Research and Critics University, 2021)
The economy of Banten Province has experienced a shift, namely from the dominance of agriculture to industry. However, the role of the agricultural sector is still quite important, although its contribution to the gross regional domestic product (GDP) continues to shrink, the absorption of labor still exceeds the industrial sector and other sectors. In other words, most of the Banten population still relies on the agricultural sector for their livelihood. The problem is the existence of the agricultural sector is still dominated by the food crops sub-sector, especially rice farming. In fact, based on the analysis of farming, rice cultivation does not provide much benefit. Other sub-sectors such as plantations, horticulture, livestock and fisheries have also not shown encouraging contributions, both to the condition of farmers and to the regional economy of Banten. So, is there a strategy to improve the condition of these farmers? The strategy is expected to be a 'panacea' so that it can 'cure' the agricultural sector which is 'chronically ill'. This research aim to investigates the impact of digital marketing to raising intention to buy agriculture product in the community can gain profit and able to fulfilled they basically needs. 30 (thirty) consumer in Serang city are taken as samples in quantative research, quistionaire use as method for gaining data. Result shown 61,4% digital marketing impact the intention to buy agriculture product.